Isn't this what I did? I think I may have messed up my notation a bit but I have x'(t) = 2t then x'(0) = 0; y'(t) = 2t-1 then y'(0) = -1; z'(t) = 1 then z'(0) = 1;
So here since the point (1,0,1) corresponds to g(t) when t is 0 we can use the value of the partial at (1,0,1) as the value of fx
(x,y,z)? Which would mean at (1,0,1) fx
= 4; fy
= 1; fz
So if everything above is correct that gives me: 4*0 + 1*(-1) + 0*1 = -1.
Also, does that mean (if this is all correct) this method can only be used if the point the partials are evaluated at and the value of t are directly related as in this example, correct?